Insights about the structure of farnesyl diphosphate synthase (FPPS) and the activity of bisphosphonates on the proliferation and ultrastructure of Leishmania and Giardia - Ana Paula R. Gadelha; Claudia Maia Brigagao; Martha Barros da Silva; Aline Beatriz Mello Rodrigues; Ana Carolina Ramos Guimarães; Fernando Paiva; Wanderley de Souza; Cristina Henriques (Parasites & Vectors, 2020)
Abstract Background The enzyme farnesyl diphosphate synthase (FPPS) is positioned in the intersection of different sterol biosynthesis pathways such as those producing isoprenoids, dolichols and ergosterol. FPPS is ubiquitous in eukaryotes and is inhibited by nitrogen-containing bisphosphonates (N-BP). N-BP activity and the mechanisms of cell death as well as damage to the ultrastructure due to N-BP has not yet been investigated in Leishmania infantum and Giardia. Thus, we evaluated the effect of N-BP on cell viability and ultrastructure and then performed structural modelling and phylogenetic analysis on the FPPS enzymes of Leishmania and Giardia. Methods We performed multiple sequence alignment with MAFFT, phylogenetic analysis with MEGA7, and 3D structural modelling for FPPS with Modeller 9.18 and on I-Tasser server. We performed concentration curves with N-BP in Leishmania promastigotes and Giardia trophozoites to estimate the IC50 via the MTS/PMS viability method. The ultrastructure was evaluated by transmission electron microscopy, and the mechanism of cell death by flow cytometry. Results The nitrogen-containing bisphosphonate risedronate had stronger anti-proliferative activity in Leishmania compared to other N-BPs with an IC50 of 13.8 µM, followed by ibandronate and alendronate with IC50 values of 85.1 µM and 112.2 µM, respectively. The effect of N-BPs was much lower on trophozoites of Giardia than Leishmania (IC50 of 311 µM for risedronate). Giardia treated with N-BP displayed concentric membranes around the nucleus and nuclear pyknosis. Leishmania had mitochondrial swelling, myelin figures, double membranes, and plasma membrane blebbing. The same population labelled with annexin-V and 7-AAD had a loss of membrane potential (TMRE), indicative of apoptosis. Multiple sequence alignments and structural alignments of FPPS proteins showed that Giardia and Leishmania FPPS display low amino acid identity but possess the conserved aspartate-rich motifs. Conclusions Giardia and Leishmania FPPS enzymes are phylogenetically distant but display conserved protein signatures. The N-BPs effect on FPPS was more pronounced in Leishmania than Giardia. This might be due to general differences in metabolism and differences in the FPPS catalytic site.